2021
DOI: 10.1007/s11365-021-00773-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of bankruptcy regimes on entrepreneurship and innovation. Is there any relationship?

Abstract: The literature review indicates that bankruptcy law may play an important role in and be one of the factors influencing the development of entrepreneurship, innovation, and thus economic growth, among other things. In previous studies, the analysis of the impact of bankruptcy law on individual variables has been conducted independently. Our aim was to conduct a holistic analysis, taking several factors into account simultaneously. Therefore, a descriptive model was proposed, based on which the following resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The innovation of enterprise management model in various industries is showing diversification, appearing one after another in various forms [13]. Since the innovation of enterprise management mode provides new paths and possibilities for enterprise development, new enterprise management modes will inevitably emerge one after another in the future enterprise competition [14].…”
Section: Introductionmentioning
confidence: 99%
“…The innovation of enterprise management model in various industries is showing diversification, appearing one after another in various forms [13]. Since the innovation of enterprise management mode provides new paths and possibilities for enterprise development, new enterprise management modes will inevitably emerge one after another in the future enterprise competition [14].…”
Section: Introductionmentioning
confidence: 99%
“…There is a higher level of risk tolerance among entrepreneurs and accordingly higher levels of entrepreneurship and innovation in countries with an effective and steady legal system promoting a debtor-friendly bankruptcy law lead to higher risk acceptance among entrepreneurs (Prusak et al, 2022). Acharya and Subramanian (2009) concluded that creditor-friendly bankruptcy laws are the cause and effect of more liquidations and, subsequently, fewer innovations, while a debtor-friendly system supports businesses to continue as going concerns.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Cooperation and innovation are considered as key success factors for development in regions (Štefenberga, 2019). Researchers have analysed the impact of bankruptcy regimes on entrepreneurship and innovation and were looking is there any relationship (Prusak et al, 2022) analysed product and service innovation in Portugal where are indicating several patterns and specificities (Costa, Rocha, & Madeira, 2022) and have paid attention on listening to the buzz and exploring the link between firm creation and regional innovative atmosphere as reflected by social media (Corradini, Folmer, & Rebmann, 2022). Endogenous development of green finance and cultivation mechanism of green bankers are investigated in big detalisation degree (Zhang et al, 2022).…”
Section: Theoretical Findingsmentioning
confidence: 99%